THE IMPACT OF MOTIVES AND CHANNELS ON THE ATTITUDE WHILE ASSESSING SOCIAL MEDIA - Yajid, Mohd Shukri Ab; shukri, Sakinah mohd; Khatibi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
The aim of current study is to inspect the influence of motives and channels on the attitude of the student while assessing the social media. Data were collected from the universities that are located in Malaysia and SPSS was engaged to examine the hypothesis. The outcomes show that positive connection among the motives, channels and the attitude of the student while assessing the social media.